Referents, tensions and identities ruptures.Professional women and their families of origin - Castañeda-Rentería, Liliana I. (2015)
This article aims to describe and analyze the processes of subjective construction of professional women in the frame of intra-family relations. The aforementioned based on practices, meanings and senses that constitute these women as women and the way how they attribute feminine identities of genre from different places and experiences of being, to fell and live as woman and the senses that the femininity acquires in this context.In particular this document aims to show the role of each families of these women had in the shaping of their genre identity and in the way in which women live and are formed. The present document distinguishes in a significant way the nearness of some subjects of study with their parents, as well as the widening of the mother feminine image in model and anti-model of what it means and implies being and live as a woman.The empirical information was obtained through 21 interviews of professional women without children in Guadalajara, Mexico.